The Role Of Electronic Word Of Mouth In Improving Product Purchase Decisions Which Social Media Activities, Easy Transactions, Product Quality, And Giveaway Promotions At The Kerinci Chic Shoes Store influence - Sarmigi, Elex; Rahayu, Sri; Arum, Enggar Diah Puspa; Wijaya, Rico; Wahyuni, Endah Sri (Jurnal Computech & Bisnis (e-journal), 2024)
This research aims to determine whether social media activities, ease of transactions, product quality, and giveaway promotion can influence purchasing decisions directly or indirectly mediated by electronic word of mouth (E-WOM). This research uses a quantitative approach with primary data collected with the help of an online questionnaire using Google Forms. The population of this research is Chic Shoes Shop customers, with a sample of 104 buyers. This research data was analyzed using the Structural Equation Model (SEM) using the SmartPLS 3.2.9 application. This research found that product quality directly positively and significantly affects purchasing decisions. Meanwhile, social media activities, ease of transactions, giveaway promotions, and word of mouth cannot influence purchasing decisions directly. This research also found that social media activities, product quality, and giveaway promotion positively and significantly affected E-WOM. In contrast, ease of transactions did not significantly affect purchasing decisions directly. This research also found that E-WOM cannot mediate the relationship between social media activities, product quality, ease of transactions, and giveaway promotion on purchasing decisions.